Knowledge Management: A Hidden Aspect in Hospitality Industry: Exploring the Necessity of Knowledge Management in the Hospitality and Tourism Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nowadays, the commercial scenery is altering rapidly and the competitive atmosphere is no longer anticipated. Existence and success rely completely on the establishment's capability to fine-tune to the dynamics of the business environment by building effective decision-making and right application of abilities and knowledge of workforces. These are current advances that denote the gratitude of knowledge as a crucial competitive apparatus for the hospitality and leisure industry sector because need to upgrade their client service to a much higher plane in order to continue in this competitive milieu. Tourism, as one of the world’s chief financial sectors will eventually be obligatory to adjust to these changes. But, hospitality and tourism industry has been sluggish in implementing KM approach. Therefore, recommendation if hospitality and tourism sector as an activity-based service sector that information and knowledge are essential want to stay competitive in this dynamic period, the adoption of a knowledge management methodology will be prerequisite. This paper presents an outline of the relatively different notion of knowledge management and the problems in implementing such an approach to a sector such as hospitality and tourism.